Energy Solutions for Forcibly Displaced Persons and Their Host Communities : Closing the Financing Gap - Patel, Laura; Nielsen, Sara Trab (World Bank, Washington, DC, 2020)
Societies require energy to function. Basic energy services like heat and light for schools and hospitals support and enrich individual and community life. Yet millions of people worldwide are overlooked in energy access agendas, particularly the 70.8 million forcibly displaced persons. Their numbers are expected to rise as conflict and climate change persist. Collaboration among host nations, development agencies, and the private sector to close financing and capacity gaps is urgently required if countries are to attain universal energy access by 2030, as called for in the international Sustainable Development Goals.